PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI KUALITAS SISTEM INFORMASI, KUALITAS LAYANAN INFORMASI, PERSEPSI KEMUDAHAN PENGGUNA, PERCEIVED USEFULNESS, DUKUNGAN TOP MANAGER, COMPUTER SELF-EFFICACY DAN KEMAMPUAN TEKNIS PERSONAL SISTEM INFORMASI AKUNTANSI TE - Anggraini, Lila; Fitrios, Ruhul (Jurnal Ekonomi Dan Bisnis, 2024)
This study aims to analyze the effect of information system quality, information service quality, perceived usefulness, top manager support, and technical capabilities of accounting information system personnel on user satisfaction of accounting information systems. The population in this study were 21,145 MSMEs in Pekanbaru City. The sampling technique used purposive sampling. Determination of the sample using the slovin formula so that a sample of 100 MSMEs was obtained with a total of 300 respondents. The data used is primary data and analyzed using the Structral Equation Model (SEM) with the SmartPLS analysis tool. The results of this study indicate that information system quality, information service quality, perceived usefulness, top manager support, and AIS personal technical ability affect AIS user satisfaction.